EVALUASI KINERJA BADAN PERMUSYAWARATAN DESA DALAM PENYELENGGARAAN DEMOKRASI DESA DI DESA BARAMBANG KECAMATAN SINJAI BORONG KABUPATEN SINJAI - Supriadi, Supriadi; Jusniaty, Jusniaty; Mursak, Mursak; Abdillah, Ashar; Nawir, Adi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to evaluate the performance of the Village Consultative Body (BPD) in implementing village democracy in Barambang Village, Sinjai Borong Subdistrict, Sinjai Regency. The BPD has a strategic role in village administration, namely legislative, supervisory, and community aspiration absorption functions. However, in its implementation, there are still various obstacles, such as low community participation, suboptimal oversight functions, and weak coordination with the village government. This study uses a qualitative approach with a participatory method. Data collection techniques include in-depth interviews, observation, and documentation. The main informants include BPD members, the village head, community leaders, and villagers. The evaluation is based on input, process, output, and outcome performance indicators. The results of the study show that the Barambang Village Council has performed its functions quite well. In its legislative function, the Village Council has consistently established five village regulations during the 2022-2023 period, covering the Village Budget (APBDesa), Village Work Plan (RKPDesa), and amendments to the Village Budget, with an increase in productivity from two regulations (2022) to three regulations (2023). The function of absorbing aspirations was carried out through a structured mechanism with a good documentation and follow-up system, supported by 16 coordination meetings during the 2022-2024 period. The supervisory function was carried out comprehensively, from planning to the realization of village government activities with coordination.